2009
DOI: 10.1007/978-3-642-03655-2_37
|View full text |Cite
|
Sign up to set email alerts
|

Situating Productive Play: Online Gaming Practices and Guanxi in China

Abstract: Abstract. Economic activities in and around online gaming in China are often correlated in the West with practices of gold farming, or selling in-game currency to players for real money in online games. What can we learn about online gaming in China and about online gaming and online sociality more broadly when we look at economic and other "pragmatic" practices through which online gaming becomes meaningful to players? In this paper, we present findings from an ethnographic study of online gaming in China's u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Lindtner et.al. [16] [17] found that many urban young Chinese players establish close social ties through game play in Internet cafés [16] and in game-related online communities [17]. These studies show that online gaming has become a meaningful way for youth to get to know friends and help each other in their offline lives.…”
Section: Related Workmentioning
confidence: 99%
“…Lindtner et.al. [16] [17] found that many urban young Chinese players establish close social ties through game play in Internet cafés [16] and in game-related online communities [17]. These studies show that online gaming has become a meaningful way for youth to get to know friends and help each other in their offline lives.…”
Section: Related Workmentioning
confidence: 99%
“…Our use of the neoliberal framework in this context is applicable because both guilds studied were comprised of North American players. However, it is possible that differences in offline culture could contribute to differences in online behaviors [20,27]. Though the present study is not comparative, it offers important insights regarding the effects of offline culture on online practices.…”
Section: Discussionmentioning
confidence: 94%
“…Areas of investigation include observing how pervasive and ubiquitous technologies gain new forms and uses when transported to new places (e.g. [15]). Significant theoretical questions have been raised about how transnationals appropriate technology, and the interplay of new technologies with mobility, hybridity, identity, culture, and local-global interconnectedness [24].…”
Section: Technology and Transnationalismmentioning
confidence: 99%